1993
DOI: 10.1007/bf01955053
|View full text |Cite
|
Sign up to set email alerts
|

Immunological responses in an infant after cyclosporine A exposure during pregnancy

Abstract: Pregnancy in transplant recipients is not uncommon. Cyclosporin A may be used as an immunosuppressive drug in these patients. Almost no data exist on the effects of cyclosporin A on the immune system of infants who have been exposed to this drug in utero. The infant of a liver transplant recipient was followed during the first 2 years of life. Shortly after birth all lymphocyte subsets were low, especially for B-cells. The distribution of lymphocytes returned to low normal ranges within the first 2 years of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…However, immunologic alterations have been observed up to 1 year of age among children born to mothers on immunosuppressive drugs (8,42). This might indicate that the immune system recovery of infants exposed to immunosuppressive drugs during pregnancy can vary and sometimes it can take longer than 12 months.…”
Section: Discussionmentioning
confidence: 98%
“…However, immunologic alterations have been observed up to 1 year of age among children born to mothers on immunosuppressive drugs (8,42). This might indicate that the immune system recovery of infants exposed to immunosuppressive drugs during pregnancy can vary and sometimes it can take longer than 12 months.…”
Section: Discussionmentioning
confidence: 98%
“…Globally, the incidence of neonatal complications is lower than with other immunosuppressive drugs. A few reports suggest hematological disorders: the T-cell counts are either increased or decreased with a CD4+/CD8+ ratio always at a higher than normal level, even after 24 months of follow-up [38]. However, there is no clinical sign of immunosuppression, no increased incidence of infections, either opportunistic or chronic and a normal IgG-antibody response to vaccination [38][39][40].…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%
“…The severity of the mother's condition was reflected by the need to replace the graft 8 days after delivery (131). Lymphopenia was detected in an infant exposed to cyclosporin in utero, and further studies revealed an increased CD4/CD8 ratio in this infant (132). In another study, antenatal exposure to cyclosporin exerted a minimal effect on fetal immune development, and had less impact on T lymphocytes than azathioprine did (94).…”
Section: Immunc?suppressionmentioning
confidence: 98%